Copy when uncertain: lower light levels increase trail pheromone depositing and reliance on pheromone trails in ants. (October 2019) - Jones, Sam; Czaczkes, Tomer J.; Gallager, Alan J.; Oberhauser, Felix B.; Gourlay, Ewan; Bacon, Jonathan P.
Abstract : Animals may gather information from multiple sources, and these information sources may conflict. Theory predicts that, all else being equal, reliance on a particular information source will depend on its information content relative to other sources. Information conflicts are a good area in which to test such predictions. Social insects, such as ants, make extensive use of both private information (e.g. visual route memories) and social information (e.g. pheromone trails) when attempting to locate a food source. Importantly, eusocial insects collaborate on food retrieval, so both information use and information provision may be expected to vary with the information content of alternative information sources. Many ants, such as Lasius niger, are active both day and night. Variation in light levels represents an ecologically important change in the information content of visually acquired route information. Here, we examined information use and information provision under high light levels, equivalent to a bright but overcast day, moderate light levels, simulating dusk, and darkness, equivalent to a moonless night. Ants learned poorly, or not at all, in darkness. As light levels decreased, ants showed decreasing reliance on private visual information, and a stronger reliance on social information, consistent with a 'copy when uncertain' strategy. In moderate light levels and darkness, pheromone depositing increased, presumably to compensate for the low information content of visual information. Varying light levels for cathemeral animals provides a powerful and ecologically meaningful method for examining information use and provision under varying levels of information content. Highlights: When navigating, ants can use visual or pheromone information. When these conflict, L. niger ants tend to follow visual route memories. We measured pheromone following and depositing under high, moderate and low light. Ants lay more pheromone at low light levels and follow them rather than memories. Varying light levels is a realistic way of investigating information use strategies.